Science through the Lens of Nature: Recent Advances in Biomimetic Approaches towards Pesticide Degradation - Borah, Shikha Jyoti; Gupta, Akanksha; Sahu, Prasanta Kumar; Dheer, Neelu; Kumar, Vinod (SynOpen, 2023)
The increased use of pesticides and the possible accumulation of residual pesticides can clearly have detrimental consequences on different environmental matrices and human health. As a result of this, an urgent need for remediation of pesticides has emerged in the last few decades. A biomimetic approach for the degradation of pesticides can have high potential. Biomimetic catalysts are synthetic chemical molecules which have been inspired by natural processes to mimic their structural and functional properties. This short review focuses on the synthesis of various biomimetic catalysts including metal-based materials and carbon-based materials. In this context, recent advances achieved by such biomimetic catalysts for the degradation of pesticides have been covered. It highlights the importance of adopting a biomimetic approach as it provides a green and efficient method for pesticide degradation. Furthermore, it provides useful insights into the challenges that remain to be addressed and the perspectives that can be adopted for future research.1 Introduction2 Biomimetic Catalysts2.1 Metal Oxides2.2 Metal Organic Frameworks2.3 Carbon-Based Materials2.4 MXenes2.5 Other Recent Advances3 Challenges4 Conclusion
Keywords: biomimetic; pesticide; degradation; synthetic catalysts; nanozyme